Superconducting Surge Current Limiter - Sławomir Kozak (Energies, 2021)
A superconducting fault current limiter (SFCL) for medium voltage networks cooled by a cryocooler was designed, built and tested by the current author. For the construction of this limiter, a high-temperature second generation superconducting tape (HTS 2G)—SF12100—was used. In this limiter, it is possible to change the working temperature. The possibility of changing the operating temperature allows for adjusting the parameters of the limiter to the electric power needs. Adjusting the parameters of the limiter to the power needs is a key problem to solve, resulting from the ambiguous characteristics of HTS tapes. Cooling with a cryocooler is the only solution in the case of a limiter for power industry applications. The electric power mechanism does not tolerate any liquids. After analyzing the experimental results and after analyzing the results from the numerical models of the limiter, the concepts of using superconductors to limit current in the power industry were changed: the transition from a superconducting fault current limiter (SFCL) to a superconducting surge current limiter (SSCL). Transition to the limiter operation system—surge current limitation—is associated with the reduction in the limiter operation time. The advantages of the transition from the SFCL to SSCL work system are presented.